FORMULASI PERMEN JELLY SIRSAK (Annona Muricata Linn) DENGAN JERUK SAMBAL (Citrus amblycarpa) - m ali, erwan sattu (Jurnal Sains Pertanian Equator, 2021)
Soursop fruit is a source of vitamin C, has a distinctive taste and aroma, which is sweet, sour and contains vitamins and minerals that are useful for containing a high enough water content so that it is very easy to damage during storage. Jelly candy is a candy made from water or fruit juice and gelling material, which has a transparent appearance and has a certain texture and elasticity. One of the factors that affect the quality of jelly candy is gelling material (hydrocolloid). The study was conducted on different concentrations of chili orange to get soursop jelly candy with chewy consistency and quality according to SNI (Indonesian National Standard). This study aims to obtain the right concentration of soursop juice and chili orange juice in the manufacture of soursop juice jelly candy based on physicochemical and sensory characteristics. This study used a randomized block design with 1 treatment factor, namely the concentration of chili orange which consisted of 6 levels of treatment with 3 replications for each treatment so that 18 samples were obtained. The results showed that the best treatment was found in the concentration of 80 grams of soursop juice, 20 grams of chili orange with physicochemical test results in the form of water content (15.40 %), ash content (0.49 %), hardness level (0.21 kg force). . The best sensory characteristics of jelly are color 3.7 (slightly yellow), sweetness 2.93 (sweet), soursop aroma 2.73 (yes), texture 2.83 (slightly chewy) favorite 3.43 (like).Keywords: Orange chili sauce, Jelly candy, Soursop